Schoolchildren as Intermediaries : Fights over Children, Education and Power in Hamar on Ethiopia's Southwestern Frontier - Maurus, Sabrina (Zeitschrift für Ethnologie, 2022)
Compulsory schooling has become a social good that is so much taken for granted that it is hardly criticized anymore. Due to the prevalence of this norm, the paradoxical effects of its global implementation are often overlooked. Drawing on ethnographic fieldwork in Hamar District, southwest Ethiopia, this paper analyses why ‘schooling for all’ that is supposed to bring development and a better life is violently contested among agro-pastoralists in Hamar. Along with the expansion of ‘Western’-style schooling, school-educated youth unemployment is increasing, and the attempt to implement compulsory schooling has created a violent conflict in Hamar District. Following the lives of first-generation schoolchildren from agro-pastoral families, this article shows how schoolchildren become intermediaries between their agro-pastoral kin and the Ethiopian government. Both groups use children and education in struggling over power and change, which creates dilemmas for school-educated youths who are related to both groups and have to navigate these political tensions throughout their life courses. The violent conflict over the implementation of compulsory schooling in Hamar District shows how schooling can turn not only into a metaphorical arena but into a literal battlefield, in which the relations between agropastoralists, the state and (inter)national development are negotiated. Various actors claim competing rights to decide about young people’s education and schooling, but young people are also taking their own decisions about their lives. These educational decisions about learning in and outside school shape wider social, political and economic processes. The increasing number of schoolchildren from agro-pastoralist families blurs the boundaries between agro-pastoralists and the central government, making it fruitful to integrate the study of schooling into research on infrastructure and politics in order to understand processes of rural transformations and conflicts. Young people mediate multiple and at times antagonistic visions of future livelihoods and corresponding forms of education, which creates dilemmas and conflicts throughout their life courses that need to be taken into account in developing sustainable ways of education beyond schooling.
Keywords: School; pastoralism; childhood; Education; Ethiopia